The Impact of the Triglyceride-Glucose Index on Poor Prognosis in NonDiabetic Patients Undergoing Percutaneous Coronary Intervention - Yang, Jie; Tang, Yi-Da; Zheng, Yitian; Li, Chen; Zhou, Qing; Gao, Jun; Meng, Xiangbin; Zhang, Kuo; Wang, Wenyao; Shao, Chunli (Frontiers in Endocrinology, 2021)
Background: The triglyceride glucose index (TyG index) is a valuable marker for predicting adverse cardiovascular events in diabetic patients. However, for nondiabetic patients, whether the TyG index is independently related to poor prognosis remains unclear. This cohort study assessed the association of the TyG index with future cardiovascular risk in nondiabetic subjects who received percutaneous coronary intervention (PCI). Methods: We consecutively enrolled 5,489 nondiabetic patients who underwent PCI. All experimental subjects were divided into 3 groups based on their TyG index, which was determined by the equation ln (fasting triglyceride (mg/dL) × fasting blood glucose (mg/dL)/2). The primary endpoint was major adverse cardiovascular and cerebrovascular events (MACCEs), including all-cause death, nonfatal myocardial infarction (MI), nonfatal stroke, and target vessel revascularization (TVR). Results: A total of 386 MACCEs were documented during a median 29-month follow-up. The Kaplan–Meier survival results indicated that among the three groups, there was no obvious difference in any endpoints. Further Cox regression analyses suggested that the TyG index was not independently related to adverse cardiovascular outcomes for nondiabetic patients who underwent PCI (HR: 0.77, 95% CI, 0.56-1.16, P=0.210 for MACCE). Subgroup analysis suggested that the TyG index was independently relevant to MACCEs for patients with low-density lipoprotein cholesterol (LDL-C) lower than 1.8 mmol/l. Conclusion: The TyG index is not an effective predictive factor for adverse cardiovascular prognosis in nondiabetic patients who underwent PCI. Subjects with LDL-C lower than 1.8 mmol/l may be at a greater risk of future cardiovascular risk.